1998
DOI: 10.1136/bmj.316.7128.361
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners' perceptions of the route to evidence based medicine: a questionnaire survey

Abstract: Objectives: To determine the attitude of general practitioners towards evidence based medicine and their related educational needs. Design: A questionnaire study of general practitioners. Setting: General practice in the former Wessex region, England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

64
564
8
32

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(676 citation statements)
references
References 18 publications
64
564
8
32
Order By: Relevance
“…In the past decade few studies have analysed the impact of clinical practice guidelines and EBM among GPs [8,10,12]. Some reviews have suggested headache evidence-based diagnostic and therapy evaluation [5,7] and optimal strategy for managing acute headache [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade few studies have analysed the impact of clinical practice guidelines and EBM among GPs [8,10,12]. Some reviews have suggested headache evidence-based diagnostic and therapy evaluation [5,7] and optimal strategy for managing acute headache [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed general practitioners' (GPs) perceptions of EBM and its influence on health care decisions [8][9][10], but to the best of our knowledge no information is available about its evaluation on migraine and information on this topic is needed because patients with migraine headaches often present family physicians with diagnostic and therapeutic challenges. Therefore, the purpose of the present study is to identify if GPs in Italy are aware of technical terms used in EBM and what their behaviour is in terms of treating patients with migraine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, la práctica de un cuidado de salud basado en la evidencia, con sus "clásicas etapas" (formulación de la pregunta, búsqueda de la información, análisis crítico, aplicación), parece no ser la alternativa preferida por muchos profesionales de la salud debido, en gran parte, a limitaciones en el tiempo para practicarla [7][8][9] . Por esta razón es que muchos profesionales de la salud, en especial en la atención primaria, prefieren utilizar resúmenes basados en evidencia generados por otros y Guías de Práctica Clínica (GPC) para la aplicación de los principios de la MBE 7,10,11 .…”
unclassified
“…Despite the promotion of NNT as easier for clinicians to understand, when presented with a range of measures of treatment effects, most found NNTs no easier to understand or explain to others than relative risk. 2 …”
mentioning
confidence: 99%